DEVELOPMENT OF MANAGERIAL COMPETENCE OF HEADS OF EDUCATIONAL INSTITUTIONS IN CRISIS CONDITIONS - Bodak, Valentina; Miliaieva, Valeria; Pantiuk, Mykola; Prystai, Olha; Burkovska, Zoriana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the crisis conditions of challenges and restrictions caused by the Covid-19 pandemic and the martial law in Ukraine, it is important to ensure stability and efficiency in the management of educational institutions. It is possible due to the condition of development of managerial competence of managers. We consider the managerial competence of educational institutions leaders is a personal phenomenon. It combines psychological, theoretical and practical readiness for managerial activities in the specific conditions of the institution's existence. For the development of managerial competence, appropriate conditions are important, as well as an actual profile, the structure of which includes: development orientation; emotional intelligence; cooperation; ability to create a safe environment; organizational capacity. As a result of the actualization of the crisis situation, the public demand for managers-leaders is increasing, hence the need to analyze, develop a theory and use leadership strategies by the heads of general secondary education institutions, since they are the basis of the manifestation of their managerial competence in crisis conditions. Our research was organized during 2018/2021 (n 112.) It showed a contradiction between the need for development and the lack of managerial competence and leadership strategies among managers in the field of education. In order to develop this property, a program of psychological and pedagogical support was developed and implemented. The results of the program's implementation confirmed its effectiveness and made it possible to conclude that the development of managerial competence can effectively take place within the limits of individual trajectories of professional growth of heads of institutions in the field of education.